Notes in the study of proverbs in vernacular used in everyday communication - Granbom-Herranen, Liisa (Portugal, 2025)
Proverbs belong to everyday communication. In the vernacular, a proverb lives as long as it is referred to. A proverb is used or referred to as either a proverb itself or the use of a proverb lends added value to the ongoing situation. The situation can be understood as a speech event or vernacular text. The perspective is based on folkloristic paremiology. In folklore studies the perspective to proverbs comes from people's way understanding and use them. Ordinary people, a folk, does not (or should not) follow the academic parlance. It is both a folkloristic and paremiologic challenge to chart proverbs which people have used and are using in their everyday practices. Proverb users, collectors, archivists, and researchers are a part of this process. Each step of the process has its own influence on the collected material. The challenge how to find relevant research material takes centre stage in studying vernacular proverbs in context.
In folklore studies the perspective to proverbs comes from people's way understanding and use them. Ordinary people, a folk, does not (or should not) follow the academic parlance. It is both a folkloristic and paremiologic challenge to chart proverbs which people have used and are using in their everyday practices. Proverb users, collectors, archivists, and researchers are a part of this process. Each step of the process has its own influence on the collected material. The challenge how to find relevant research material takes centre stage in studying vernacular proverbs in context.
We do not know which proverbs (and how and why) have been used in the earlier times. We know only collected and recorded ones. Source criticism can be seen as an integral part of establishing a realistic picture of the material that is used in paremiologic studies.